Experiences of patients and healthcare professionals of NHS cardiovascular health checks: a qualitative study - Riley, Ruth; Coghill, Nikki; Montgomery, Alan A.; Feder, Gene; Horwood, Jeremy (Oxford University Press, 2016)
Background